2020
DOI: 10.1111/bre.12501
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic control on mass‐transport deposit and canyon‐fed fan system in the Ulleung Basin, East Sea (Sea of Japan)

Abstract: Mass-transport deposits (MTDs) and submarine fan complexes are the results of gravity-induced sedimentary flows occurring mainly in deep-water environments (Bouma,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
(233 reference statements)
0
3
0
Order By: Relevance
“…Aggradational channels form in high accommodation regimes in the lower course of relatively steep out‐of‐grade systems (Pirmez et al ., 2000; Kneller, 2003; Samuel et al ., 2003; Hodgson et al ., 2011) and up‐dip of topographic obstacles (growing tectonic or salt‐related structures, mass transport deposits, and a combination thereof) due to flow blocking by (Kane et al ., 2012; Hansen et al ., 2015, 2017; Torres Carbonell & Olivero, 2019; Watson et al ., 2020; Park et al ., 2021; Tek et al ., 2021) or in systems at grade in which an equilibrium sinuosity has been reached and overspilling of finer‐grained sediments promotes levee aggradation (Peakall et al ., 2000). Alternatively, Kneller (2003) proposed that changes in flow parameters towards less dense, thick and finer‐grained flows might force a channel to aggrade, irrespective of its along dip profile.…”
Section: Discussionmentioning
confidence: 99%
“…Aggradational channels form in high accommodation regimes in the lower course of relatively steep out‐of‐grade systems (Pirmez et al ., 2000; Kneller, 2003; Samuel et al ., 2003; Hodgson et al ., 2011) and up‐dip of topographic obstacles (growing tectonic or salt‐related structures, mass transport deposits, and a combination thereof) due to flow blocking by (Kane et al ., 2012; Hansen et al ., 2015, 2017; Torres Carbonell & Olivero, 2019; Watson et al ., 2020; Park et al ., 2021; Tek et al ., 2021) or in systems at grade in which an equilibrium sinuosity has been reached and overspilling of finer‐grained sediments promotes levee aggradation (Peakall et al ., 2000). Alternatively, Kneller (2003) proposed that changes in flow parameters towards less dense, thick and finer‐grained flows might force a channel to aggrade, irrespective of its along dip profile.…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, this two-stage tectonic scenario is most widely referred to as the evolutionary framework of the Ulleung Basin (Bahk et al, 2017;Cukur et al, 2018;Park et al, 2019;Horozal et al, 2021;Park et al, 2021). However, the scenario omits the final tectonic phase of the East Sea, marked by the nucleation of a new embryonic subduction system under E-W compressional stress since the Early Pliocene.…”
Section: Regional Settingmentioning
confidence: 99%
“…Some researchers thought that the folds in Tsushima are the onshore part of the Taiwan-Shinji fold belt (Itoh & Nagasaki, 1996), which was formed mainly in the latest Miocene (Cukur et al, 2011;Gungor et al, 2012;Kong et al, 2000;Lee et al, 2006Lee et al, , 2011Tanaka & Ogusa, 1981). However, Korean geologists revealed that the folding began at 12 Ma (Figure 16) (Kim et al, 2019;Lee et al, 2001Lee et al, , 2011Park et al, 2020;Yoon et al, 2002Yoon et al, , 2003. It means that the folding in the belt was not simultaneous with the main phase of the folding in Tsushima (Figure 16).…”
Section: Implications For Regional Tectonicsmentioning
confidence: 99%